Progression of blood-borne viruses through bloodstream: A comparative mathematical study. (April 2023) - Ram, Daya; Bhandari, D.S.; Sharma, Kushal; Tripathi, D.
Highlights: A mathematical model is developed to examine the progression of bloodborne viruses through blood flow. A comparative study for movement of HIV, HBV and HCV through blood flow is presented. BBO equation is taken into account for the simulation of movement of bloodborne viruses through blood flow. Couple stress fluid model is considered for the blood to see the rheological nature of blood. Simulation reported that progression of bloodborne viruses through blood flow is slower for high viscous blood, non-Newtonian nature of blood and larger size of the viruses. Abstract: Background and Objectives: Blood-borne pathogens are contagious microorganisms that can cause life-threatening illnesses, and are found in human blood. It is crucial to examine how these viruses spread through blood flow in the blood vessel. Keeping that in view, this study aims to determine how blood viscosity, and diameter of the viruses can affect the virus transmission through the blood flow in the blood vessel. A comparative study of bloodborne viruses (BBVs) such as HIV, Hepatitis B, and C, has been addressed in the present model. A couple stress fluid model is used to represent blood as a carrying medium for virus transmission. The Basset-Boussinesq-Oseen equation is taken into account for the simulation of virus transmission. Methods: An analytical approach to derive the exact solutions under the assumption of long wavelength and low Reynolds number approximations is employed. For the computation of the results, a segment (wavelength) of blood vessels about 120 mm with wave velocities in the range of 49 − 190 mm / sec are considered, where the diameter of BBVs ranges from 40-120 nm. The viscosity of the blood varies from 3.5-5.5 × 10 −3 Ns / m 2 which affect the virion motion having a density range 1.03 − 1. 25 g / m 3 . Results: It shows that the Hepatitis B virus is more harmful than other blood-borne viruses considered in the analysis. Patients with high blood pressure are highly susceptible for transmission of BBVs. Conclusions: The present fluid dynamics approach for virus spread through blood flow can be helpful in understanding the dynamics of virus propagation inside the human circulatory system.